Linguistic analysis of plain language summaries and corresponding scientific summaries of Cochrane systematic reviews about oncology interventions - Jelena Šuto; Ana Marušić; Ivan Buljan (Cancer Medicine, 2023)
Abstract Background Cochrane plain language summaries (PLSs) are an important format to present high‐quality healthcare evidence to patients with cancer and their families. They should be written in a way everyone can understand, since they serve as a tool in decision‐making and present a bridge to overcome the gap between the healthcare users and professionals. Objective The aim of the study was to assess the language characteristics of PLSs of Cochrane systematic reviews of oncology interventions in comparison with corresponding Cochrane scientific abstracts (SAs). Methods In this cross‐sectional study, we included all Cochrane PLSs and SAs of systematic reviews of oncology interventions available in the Cochrane Database of Systematic Reviews. We assessed text readability, measured using the Simple Measure of Gobbledygook (SMOG) index, and the prevalence of words related to different language tones (clout, authenticity, emotions and analytical tones). Two independent assessors categorized the conclusiveness of the efficacy of interventions into nine categories. Results The overall median SMOG index for 275 PLSs was 13.0 (95% confidence interval [CI] 12.8–13.3). Readability scores did not differ across Cochrane Review Groups. SAs had a higher readability index than the corresponding PLSs (median = 16.6, 95% CI = 16.4–16.8). Regarding linguistic characteristics, PLSs were shorter than SAs, with less use of analytical tone, but more use of a positive emotional tone and authenticity. Overall, the ‘Unclear’ category of conclusiveness was the most common among all PLSs. Also, PLSs with ‘No evidence’ conclusions were the shortest and had the lowest SMOG index. Conclusion PLSs of Cochrane systematic reviews of oncological interventions have low readability and most give unclear conclusions about the efficacy of interventions. PLSs should be simplified so that patients and their families can benefit from appropriate health information on evidence synthesis. Further research is needed into reasons for unclear language to describe evidence from oncology trials.